Agricultural systems regulate plant and insect diversity and induce ecosystem novelty. (March 2023) - Woodbridge, Jessie; Fyfe, Ralph; Smith, David; de Varielles, Anne; Pelling, Ruth; Grant, Michael J.; Batchelor, Robert; Scaife, Robert; Greig, James; Dark, Petra; Druce, Denise; Garbett, Geoff; et al.
Abstract: Land-use change plays an important role in shaping plant and insect diversity over long time timescales. Great Britain provides an ideal case study to investigate patterns of long-term vegetation and insect diversity change owing to the existence of spatially and temporally extensive environmental archives (lake sediments, peatlands, and archaeological sites) and a long history of landscape transformation through agrarian change. The trends identified in past environmental datasets allow the impacts of land-use change on plant and insect diversity trends to be investigated alongside exploration of the emergence of ecological novelty. Using fossil pollen, insect (beetle), archaeodemographic, archaeobotanical and modern landscape datasets covering Britain, similarities are identified between insect diversity and pollen sample evenness indicating that vegetation heterogeneity influences insect diversity. Changing land use captured by archaeobotanical data is significantly correlated with pollen diversity demonstrating the role of human activity in shaping past diversity trends with shifts towards ecosystem novelty identified in the form of non-analogue pollen taxa assemblages (unique species combinations). Modern landscapes with higher agricultural suitability are less likely to have pollen analogues beyond the last 1000 years, whilst those in areas less suited to agriculture and on more variable topography are more likely to have analogues older than 1000 years. This signifies the role of agriculture in the creation of novel ecosystems. Ecological assemblages characteristic of earlier periods of the Holocene may persist in areas less affected by agriculture. The last 200 years has witnessed major shifts in novelty in a low number of pollen sites suggesting that novel ecosystems emerged over a longer time period resulting from the cumulative impacts of land-use change. Highlights: Integrating past environmental archives informs about land use and diversity change. Insect and pollen diversity trends reflect disturbance caused by land-use change. Ecosystem novelty is represented by non-analogue pollen species assemblages. Novel ecosystems emerged from the cumulative long-term impacts of land-use change.